ASSESSMENT AND EVALUATION OF WASTE ELECTRIC AND ELECTRONICS DISPOSAL SYSTEM IN THE MIDDLE EAST - Hasan Alameer (European Scientific Journal, ESJ, 2014)
Electronic waste has become a challenge to most nations. The ewastechallenge can only be met by combining effective legislation withincentives to develop business and employment opportunities to maximizethe lifespan of these valuable finite natural resources. Capacity building andtechnology transfer from developed countries to developing countries, alongwith the implementation of international standards, will be a key to reducingwaste and pollution, in parallel with the creation of sustainable businessmodels. This paper attempts to review the management of WEEE in theMiddle East and propose a guiding framework for the national policies inregards to this growing problem.